Penegakkan Hukum Lingkungan Menuju Tercapainya Keadilan Lingkungan - Indah Sari (JURNAL MITRA MANAJEMEN, 2016)
AbstracThis writing is about the role of environmental-law enforcement in the esta-blishment of environmental justice. Of those that affecting ecological damage and pollution is the ignorance of environmental-law enforcement. While there are pre-ventive ways, like generating or implementing regulation on ecological con-servation; there are also repressive ways, like punishing law breakers of environmental act. Law enforcement is a way to foster environmental justice, in which people’s rights of a clean and healthy circumstances are fulfilled. Keywords: Environment, Enviromental Law, Enviromental, Law Enforcement, Enviromental Justice